STUDY OF COFFEE DRINKING CULTURE IN SEVERAL COUNTRIES IS A MARKET DIFFERENTIATION FOR EAST JAVA COFFEE EXPORT DESTINATION COUNTRIES - In'am Widiarma (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2024)
Objective – This research is motivated by assessing that the culture of drinking coffee in several countries has its own way and coffee also has its own taste. Studying the cultures of various countries shows market differentiation, you can grouping the cultures from these differences to become similar culture of the countries, in order to do International Marketing easier. Design/Methodology/Approach – The research technique was carried out using a normally distributed data technique with Pearson correlation and if not normal with Spearman correlation (the p value used was 0.05). The samples were taken from data of five large purchasing countries of coffee commodities from East Java Province. These countries are Egypt, Japan, Philippine, Malaysia and Italy. Findings – The results of the research show that the trend of East Java's export movement has a fairly strong correlation with Philippine, The Philippines is a former Spanish colony for almost 300 years, therefore Spanish culture has a strong influence on lifestyle of Filipino society. The culture is form a belief and heritage from generation to generation. Conclusion and Implications – There is a fairly strong correlation looking at the movement of trends in East Java's export realization and the value of exports to Philippine related to coffee exports by East Java. Recommendations for this research are for the East Java Regional Government to develop coffee commodity exports to former Spanish colonies such as Mexico, Colombia, Cuba, Argentina, Chile, Peru, Ecuador, Venezuela and others.